EFEKTIVITAS LATIHAN RANGE OF MOTION TERHADAP KONTRAKTUR ANAK CEREBRAL PALSY - Sri Wahyuni; Ernesta Ene (Jurnal Pelayanan Pastoral, 2024)
Range Of Motion is a technique used to treat joint problems such as shortening, stiffness, joint hypomobilization and pain, so that the joint returns to anatomically normal. Contracture is the loss or lack of full range of motion of a joint when moved passively or actively due to the limitation of fibrous tissue of the supporting tissue, muscles and skin. Cerebral palsy is a damage to the brain that affects control over the body regarding position and movement. Contractures and cerebral palsy are inseparable because brain damage causes problems in the locomotor organs, namely the arms and legs. Exercises that can be given are range of motion exercises. This study aims to assess whether range of motion exercises are effective for treating contractures in children with cerebral palsy. This study used a quantitative description research design, with the research subjects totaling 2 children with cerebral palsy who experienced contractures, namely FC and FR. The data collection method used is the observation method. Data analysis is done by comparing the results of the pre test and post test. Based on the results of processing the observation sheet (observation)) observed during the pre test and post test for FC and FR, the average difference between the initial condition and the final condition of the lowest progress obtained is 20 and the highest is 100. If you look at the ideal condition of the direction of joint motion compared to the pre-test condition, the difference is indeed far away because FC and FR have contractures due to high spasticity, but with the provision of range of motion exercises there is a change in joint motion even though it is not too much.